A worm in the cytology laboratory: A root cause analysis case study. Issue 10 (21st June 2019) - El Hussein, Siba; Guerrero, Dominick; Rozental, Stefano; Weiss, Louis M.; Gera, Shweta; Suhrland, Mark; Fatyan, Alaeddin; Khader, Samer N.
Abstract: In the spring of 2018, nematode‐like organisms were first noted at the time of microscopic diagnosis on gynecologic (GYN) and anal pap specimens in our institution's cytopathology department. Due to their morphology and specimen source, we considered a diagnosis of pinworm. However, after identifying at least 30 more cases over 3 months from patients living in variable locations, we started favoring a contaminant. This report studies the steps that were initiated to figure the source of pap smear‐preparation contamination and the molecular investigation to identify the nature of the contaminant.